Theoretical study of the discharge decomposition mechanism of environment-friendly insulation gas HFO-1234ze(E) in the presence of trace water. Issue 1 (1st May 2022) - Gan, Hui; Wang, Feng; Zhong, Lipeng; Liu, Jie; Hai, Bin; Tang, Nian; Li, Li
Abstract: HFO-1234ze(E) has excellent insulating and environmental properties, but its discharge decomposition mechanism in the presence of trace water is still unclear. Based on the density functional theory (DFT), the discharge decomposition characteristics of HFO-1234ze(E) in the presence of trace water were analyzed at the B3LYP/6-311+G(d, p) level. The results show that in the presence of trace water, HFO-1234ze(E) will decompose and generate H2, HF, CH≡CF, CH≡CH, CF3 OH, CF3 H, CF4, C2 F6, CF2 O, CH2 =CHF and CHF2 CH3 . By analyzing the ionization parameters of the main decomposition products, it can be found that the dielectric strengths of most of the products were lower than that of HFO-1234ze(E). Among the products, CF3 H, CF4 and C2 F6 are hazardous to the environment, while CH2 =CHF, CHF2 CH3 and CF2 O are flammable or toxic, which may endanger the safety of staff. Therefore, water should be avoided when HFO-1234ze(E) is used as the insulating medium.